(3GdCShGb h GdNjGQGJ aj GdeLJeY GdMQ (B:s (3Gdage GdUGFH ddCehQ (B/s - (3L(B.(3HGQh, QhHQJs ((3YeGf(B: s (3OGQ GdcJGH GdMOjK(B, s, 2009)
(3Gdfeh GdEbJUGOj(B- (3GdSjGSI GdfbOjI hGdJehjdjI(B- (3GdSjGSI GdeGdjI ChGdEfaGbjI(B- (3GdVQjHI hSjGSGJ GbJUGOjI cdjI CNQi(B- (3bhI GdefWb Ch GdJYdjd GdEbJUGOjs
(3GdeQGLY U(B.147(3; cTGa GdehGVjY U(B.151s
Keywords: (3GdCShGbs; (3GdEbJUGOs; (3GdSjGSI GdfbOjIs